2008
DOI: 10.1159/000142397
|View full text |Cite
|
Sign up to set email alerts
|

Saireito and Saikosaponin D Prevent Urinary Protein Excretion via Glucocorticoid Receptor in Adrenalectomized WKY Rats with Heterologous-Phase Anti-GBM Nephritis

Abstract: Aims: In order to clarify the antinephritic mechanisms of saireito, the glucocorticoid receptor agonistic effect of saireito was evaluated in adrenalectomized rats with anti-glomerular basement membrane (anti-GBM) nephritis.Methods: Rats with anti-GBM nephritis were subjected to adrenalectomy to exclude the effects of endogenous steroid hormones to investigate effects of saireito on the nephritis. The suppressive effects of saireito and saikosaponin D on the production of cytokines were investigated in vitro a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Saikosaponin-d (SSd), an extract from a traditional Chinese herb, Bupleurum chinensis DC, exhibits various pharmacological properties, such as anti-inflammation [14,15], hepatocyte injury prevention [16], angiogenesis inhibition [17], and anti-cancer [18,19]. In our preliminary experiments, SSd and radiation are administered to treat liver cancer; the results have revealed that this combined treatment is more effective than either of these treatments administered alone.…”
Section: Introductionmentioning
confidence: 99%
“…Saikosaponin-d (SSd), an extract from a traditional Chinese herb, Bupleurum chinensis DC, exhibits various pharmacological properties, such as anti-inflammation [14,15], hepatocyte injury prevention [16], angiogenesis inhibition [17], and anti-cancer [18,19]. In our preliminary experiments, SSd and radiation are administered to treat liver cancer; the results have revealed that this combined treatment is more effective than either of these treatments administered alone.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous traditional Chinese plants have been identified to possess biological activities with potential therapeutic applications. Saikosaponin-d (SSD), a saponin derivative extracted from several species of Bupleurum (Umbelliferae), has been traditionally used in the treatment of infectious diseases due to its anti-inflammatory, antipyretic and analgesic effects (4,5). Previous studies have demonstrated that SSD also has hepatoprotective, antifibrotic (6,7) and immunomodulatory (8,9) activities.…”
Section: Introductionmentioning
confidence: 99%
“…Saikosaponins, the major bioactive ingredients of the genus Bupleurum with a long history of medicinal use, exert significant pharmacological activities, including antitumor (targeting various cancer cells) (Motoo and Sawabu, 1994;Ahn et al, 1998;Hsu et al, 2000;Tsai et al, 2002;Wen-Sheng, 2003;Hsu et al, 2004;Kim and Hong, 2011), chemosensitizing (Wang et al, 2010a), anti-inflammatory (Yokoyama et al, 1981;Nose et al, 1989a;Bermejo Benito et al, 1998), immunomodulatory (Kumazawa et al, 1989;Leung et al, 2005;Sun et al, 2009), hepatoprotective (Abe et al, 1980;Fan et al, 2007;Wu et al, 2008), antinephritic Chen et al, 2008;Hattori et al, 2008), antibacterial and antiviral (Kumazawa et al, 1990;Chiang et al, 2003;Cheng et al, 2006), estrogenic (Wang et al, 2010b), and promoting amylase secretion in rat pancreatic acini (Yu et al, 2002). On the other hand, saikosaponins have also been reported to be responsible for toxicity induced by their hemolytic action (Abe et al, 1978a, b;Nose et al, 1989b).…”
Section: Introductionmentioning
confidence: 99%